Candida strains and resistance patterns identified in a tertiary hospital - Demir, Canan (The European Research Journal, 2022)
Objectives: Candida species are the most common fungal infectious agents. Candida species are important with their increasing frequency in hospital-acquired infectious agents. The issue of antibiotic resistance, which frequently encountered in bacterial agents, is unfortunately also valid in fungal infections. In the present study, we aimed to determine the resistance of Candida species in our hospital including 1350 patient beds, the materials and units of production, and their sensitivity to antifungal drugs, in particular fluconazole. Methods: Yeast growths, colony morphology, germ tube formation and VITEK 2 Compact automated identification system detected in the samples evaluated in the central laboratory of our hospital between January 1, 2021 and December 31, 2021 were typed. Antifungal susceptibilities, especially fluconazole, caspofungin, and amphotericin B susceptibilities, were determined by an automated system. Results: In total, 2446 within the Candida growing sample was determined as 49% Candida albicans, 26.9% Candida parapsilosis, %17.9 Candida tropicalis, Candida glabrata and Candida krusei were observed in 2.3%. Although the distribution of Candida species in other intensive care units and services was comparable to the general incidence, C. albicans was detected in 38%, C. parapsilosis 30% and C. tropicalis 27% in surgical intensive care units. Moreover, C. tropicalis was the dominant species in the neonatal intensive care unit (75%). Conclusions: In the present study, C. albicans was the most common candida species, and C. parapsilosis was the second most frequently reproduced species. It has been suggested that resistance patterns differ between species and between wards, therefore species identification and susceptibility analysis are important, and these should be taken into account when starting empirical, preemptive and antifungal treatment.